Active DNA demethylation—The epigenetic gatekeeper of development, immunity, and cancer. Issue 1 (27th November 2020) - Prasad, Rahul; Yen, Timothy J.; Bellacosa, Alfonso
Abstract: DNA methylation is a critical process in the regulation of gene expression with dramatic effects in development and continually expanding roles in oncogenesis. 5‐Methylcytosine was once considered to be an inherited and stably repressive epigenetic mark, which can be only removed by passive dilution during multiple rounds of DNA replication. However, in the past two decades, physiologically controlled DNA demethylation and deamination processes have been identified, thereby revealing the function of cytosine methylation as a highly regulated and complex state—not simply a static, inherited signature or binary on‐off switch. Alongside these fundamental discoveries, clinical studies over the past decade have revealed the dramatic consequences of aberrant DNA demethylation. In this review we discuss DNA demethylation and deamination in the context of 5‐methylcytosine as critical processes for physiological and physiopathological transitions within three states—development, immune maturation, and oncogenic transformation; and we describe the expanding role of DNA demethylating drugs as therapeutic agents in cancer. Abstract : Thymine DNA glycosylase (TDG) "clears the cytosine bases" through base excision repair. DNA methyltransferases "start the ball game" by methylating cytosine at the 5‐carbon position to produce 5‐methylcytosine (5mC), which then serves as a substrate for oxidation or deamination. Left panel: In the case of oxidation, ten‐eleven translocation (TET) enzymes sequentially oxidize 5mC, first to 5‐hydroxymethylcytosine (5hmC), then to 5‐formylcytosine and finally 5‐carboxylcytosine. Both of the latter oxidation products are substrates for base excision by TDG. Right panel: In the case of deamination, 5mC is deaminated by AID/APOBEC family enzymes to thymine (T), creating a T:G mismatch—the nominal substrate for TDG. Similarly, 5hmC could possibly be deaminated to 5‐hydroxymethyluracil (5hmU), another TDG substrate. In addition to 5mC, TET enzymes can also oxidize thymine to 5hmU. Intermediates formed by either process, in particular the abasic site (AP) can be enzymatically targeted by downstream base excision repair activities (AP endonuclease, DNA polymerase β, DNA ligase). Of note, methyl‐binding domain‐4 and SMUG1 are the only other enzymes with known T:G and hmU:G base excision function, respectively.